Oral Salmon Calcitonin Improves Fasting and Postprandial Glycemic Control in Lean Healthy Rats - Feigh, M.; Nielsen, R. H.; Hansen, C.; Henriksen, K.; Christiansen, C.; Karsdal, M. A. (Hormone and Metabolic Research, 2012)
A novel oral form of salmon calcitonin (sCT) was recently demonstrated to improve both fasting and postprandial glycemic control and induce weight loss in diet-induced obese and insulin-resistant rats. To further explore the glucoregulatory efficacy of oral sCT, irrespective of obesity and metabolic dysfunction, the present study investigated the effect of chronic oral sCT treatment on fasting and postprandial glycemic control in male lean healthy rats. 20 male rats were divided equally into a control group receiving oral vehicle or an oral sCT (2 mg/kg) group. All rats were treated twice daily for 5 weeks. Body weight and food intake were monitored during the study period and fasting blood glucose, plasma insulin and insulin sensitivity were determined and an oral glucose tolerance test (OGTT) performed at study end. Compared with the vehicle group, rats receiving oral sCT had improved fasting glucose homeostasis and insulin resistance, as measured by homeostatic model assessment of insulin resistance index (HOMA-IR), with no change in body weight or fasting plasma insulin. In addition, the rats receiving oral sCT had markedly reduced glycemia and insulinemia during OGTT. This is the first report showing that chronic oral sCT treatment exerts a glucoregulatory action in lean healthy rats, irrespective of influencing body weight. Importantly, oral sCT seems to exert a dual treatment effect by improving fasting and postprandial glycemic control and insulin sensitivity. This and previous studies suggest oral sCT is a promising agent for the treatment of obesity-related insulin resistance and type 2 diabetes.
Keywords: antidiabetic drug; glycemic control; salmon calcitonin; type 2 diabetes